DISCIPLINE ANALYSIS, MOTIVATION AND PERFORMANCE: Case Study of Polri Members at the Kulonprogo Public Service Mall (2019) - Patongai, Andi Mayasari; Zulhawati; Setiawan, Bambang Moertono (Universitas Teknologi Yogyakarta, 2019)
The purpose of this research is to determine wheater discipline, motiation and job performance having high rates on Public Service in MPP Kulon Progo. The respondens are 30 from Samsat Kulon Progo consist of 10 from Satintelkan and 20 from Satlantas. Data use questionnaire with Likert scale for measurement. Queastionnaire consist of 13 for dicipline, 14 for motivation and 10 for job performance. Analysis data use means analysis that compared by normal curve score. This research aims to analyzing the indicators of each dimention with means scales. The result of the research has evidanced that firmness of disciplines, need for self esteem of motivation and job quantity of job performance have 4.43, 4.47, and 4.70 which highest means, having best category. Justice of diciplines, self actualization of motivation and attitude of job performance have 4.23, 4.25 and 4.53 whisch lowest means, having best category. The main conclution that can be drawn in this study are disciplines, motivation and job performance officer Polres Kulon Progo in MPP Kulon Progo have been very good for firmsness, self esteem and job quantity also needed enhancement on justice, self actualization and attitude for better public service.